A method of identifying health-based benchmarks for psychosocial risks at work: A tool for risk assessment. (March 2017) - Kyaw-Myint, Su Mon; Strazdins, Lyndall; Clements, Mark; Butterworth, Peter; Gallagher, Lou
Highlights: Psychosocial risks are well-recognised occupational health hazards. No critical exposure levels exist for psychosocial risks to inform risk management. We offer a method to estimate critical levels of exposure for psychosocial risks. We identify critical levels of job control using the benchmark dose method. Influence over many aspects of work is needed to reduce the risk of depression. Abstract: Objectives: We present a novel approach to identify critical exposure levels or health-based benchmarks of job control using the benchmark dose (BMD) method. This method provides benchmarks for risk assessment of psychosocial risks, similar to benchmarks used for other occupational health hazards such as chemicals. Methods: Two staged (bivariate and adjusted) BMD modelling was conducted using epidemiological data from an age-cohort study in south-eastern Australia. The adjusted BMD model incorporated age, gender, education, personality traits and mental health status at baseline. Results: Depression is a more sensitive (health compromising) outcome for job control compared to anxiety in both types of BMD modelling. For an excess risk of 5% for depression, the adjusted benchmark dose was 0.49 and the critical exposure level, being the lower one sided 95% confidence limit of the adjusted BMD, was 0.37. If workplace guidelines are based on this critical exposure level, workers need to have a minimum of ten out of 15 aspects of job control measured in this study to reduce the excess risk of depression. Conclusions: The BMD approach can identify critical exposure levels for job control. This suggests a similar approach can be used for other psychosocial risks for which no critical exposure levels are currently available. Critical exposure levels can provide guidance needed to assess risk and address psychosocial risks, similar to other health hazards. Benchmarks or critical exposure levels of psychosocial risks can assist the inspectorate and employers to conduct risk assessment of workplaces and identify areas for intervention.